The Relationship of Hearing Loss to Quality of Life in the Elderly in Nursing Homes - Addini Amira Putri; Yuliani Mardiati Lubis; OK Yulizal (Journal of Social Research, 2025)
Hearing loss is a common health concern among the elderly that significantly affects quality of life. This research investigated the link between the type and severity of hearing impairment and quality of life, utilizing the Hearing Handicap Inventory for the Elderly–Screening (HHIE-S). A cross-sectional approach was used with 58 participants aged 60 or older at the Binjai Elderly Social Service Unit of the North Sumatra Provincial Social Service. The study involved pure-tone audiometry to precisely measure each individual’s hearing, along with the HHIE-S to assess the social and emotional impacts of hearing loss. Findings revealed a strong correlation between the severity of hearing loss and HHIE-S scores (r = 0.641; p < 0.001). The Kruskal–Wallis test showed significant differences in HHIE-S scores among various hearing loss groups (p = 0.024), with the mixed hearing loss group having the highest average score. Additional analysis using the Mann–Whitney test confirmed significant differences between the normal hearing and mixed-hearing-loss groups, as well as between the conductive-hearing-loss and mixed-hearing-loss groups.